DISPARITIES IN ROMANIA'S AGRICULTURE AMONG THE REGIONS OF DEVELOPMENT - Agatha POPESCU; Toma Adrian DINU; Elena STOIAN; Valentin ŞERBAN; Adelaida HONTUS; Carmen ANGELESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The research aimed to assess the discrepancies exiting among Romania's NUTS-2 microregions of development using a large number of indicators reflecting the status of agriculture in the year 2020, 2022 and 2023, using as information source Eurostat database for which the data were available in March 2025. The research methods utilized in this study refer to: structural index, showing the share of each region in the total level or value of the studied indicator, rank-order method to identify the hierarchy of the regions, comparison method, Herfindahl-Hirschman Index(HHI) to evaluate the competitiveness/concentration among regions for each indicator. The results confirmed that in Romania there are still discrepancies among regions in the development of agriculture. The hierarchy of the regions based on the number of points accumulated for 14 main indicators is the following: Rank 1- 63 points, South Muntenia, Rank 2-66 points, North East region, Rank 3-85 points South East region, Rank 4-93 points North West region, Rank 5-117 points South West Oltenia, Rank 6-118 points Central region, Rank 7-139 points West region and Rank 8-165 points Bucharest Ilfov. HHI below 0.15 reflected a competition or lack of concentration among regions for population, labour force, intermediary consumption, factor income, entrepreneurial income; HHI between 0.15-0.25 showed a moderate competition/concentration among regions for area in organic farming, number of farms, crop and animal output, gross value added and gross capital formation. HHI greater than 0.25 reflected a high competition for GDP. Therefore, the disparities among regions still exist and leave "an empty box" for looking for solutions to create a balanced and convergent economic and social development in Romania.